PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof
By using the compound of general formula (I) as a mold scale resistance additive in PBT composite materials, the mold scale and mold rate problems caused by degradation of PBT materials under high temperature and high humidity conditions are solved, and the effect of low mold scale and rapid mold formation is achieved.
Patent Information
- Application Number
- CN202411963107.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
PBT materials are prone to degradation under high temperature and high humidity conditions, resulting in an increase in mold scale and a decrease in molding rate during injection molding, affecting the quality and production efficiency of the product.
The compound of general formula (I) is added as a mold scale resistance additive to the PBT composite material. By reacting with small molecules in the system, small molecules generated by PBT are captured, small molecules are reduced, small molecules are improved, scale problems are improved, and the crystallization temperature of the material is increased to speed up molding.
It effectively reduces the generation of mold scale during the injection molding process of PBT materials, increases the molding rate and the crystallization temperature of the materials, and comprehensively achieves the goals of low mold scale and rapid molding.
Smart Images

Figure BDA0005217665160000021 
Figure BDA0005217665160000041 
Figure BDA0005217665160000051
Abstract
Description
Technical Field
[0001] The invention belongs to PBT materials, and in particular relates to a PBT composite material and a preparation method and application thereof. Background Art
[0002] Polybutylene terephthalate (PBT) is a polyester made by polycondensation of terephthalic acid and 1,4-butanediol. It is a milky white, semi-transparent to opaque, semi-crystalline thermoplastic polyester. It has high heat resistance and can work for a long time at up to 140°C. It has good toughness, fatigue resistance, resistance to organic solvents, self-lubrication and low friction coefficient. Due to these excellent properties, it is widely used in automobiles, mechanical equipment, precision instrument parts, electronic appliances, textiles and other fields. However, PBT material itself is prone to degradation under high temperature and high humidity conditions, so it needs to be hydrolysis-resistant modified to facilitate its long-term operation under high temperature and high humidity. Glass fiber is often added to improve its hydrolysis resistance, creep resistance and other properties. However, the addition of glass fiber will make PBT material more easily decomposed into oligomers and small molecules during the injection molding process, which will significantly increase the content of small molecules. Not only will it cause more residues on the mold during the injection molding process, forming serious mold scale, but it is also necessary to regularly clean the mold scale on the mold surface during continuous processing, resulting in low production efficiency. It will also reduce the molding rate of the material and affect the appearance smoothness of the molding surface of the material. In addition, due to the residual mold scale, the molded parts will have obvious white spots and other defects in severe cases, resulting in the product failing to meet the requirements.
[0003] Therefore, there is still a need to continue to develop a PBT material with low mold deposit and fast molding rate during injection molding. Summary of the invention
[0004] In view of the problem that the PBT material injection molding process involved in the above-mentioned prior art is prone to mold deposit and low molding rate, the present invention will provide a PBT composite material and a preparation method and application thereof.
[0005] To achieve the above purpose, the following technical solutions are specifically included:
[0006] In one aspect, the present invention provides a use of a compound of general formula (I) as a mold deposit resistance additive in a PBT composite material, wherein the compound of general formula (I) is as follows:
[0007]
[0008] Wherein, X1, X2, and X3 are each selected from any one of a hydrogen atom, an alkyl group, an alkoxy group, and a halogen.
[0009] The compound of general formula (I) is a compound containing a 3-phenyl-2-acrylic acid structure. As a mold deposit resistance additive in PBT composite materials, it can react with the hydroxyl groups on the small molecules in the system, capture the small molecules generated by PBT, reduce the content of small molecules in the system, improve the mold deposit problem generated during the injection molding process, increase the crystallization temperature of the system, accelerate molding, and comprehensively achieve the goal of low mold deposit and rapid molding of PBT composite materials.
[0010] In a second aspect, the present invention provides a PBT composite material, comprising the following raw material components in parts by weight:
[0011] The PBT resin is 35-80 parts, the glass fiber is 9-31 parts, the mold deposit resistance additive is 0.4-2.2 parts, and the additive is 0.4-1.6 parts.
[0012] Preferably, the compound of general formula (I) includes at least one of 3-phenyl-2-propenoic acid, 3-(4-chlorophenyl)-2-propenoic acid, 3-(3-methylphenyl)-2-propenoic acid, and 3-(2-bromophenyl)-2-propenoic acid.
[0013] Preferably, the PBT resin is 36-78 parts, the glass fiber is 10-30 parts, the mold deposit resistance additive is 0.5-2 parts, and the additive is 0.5-1.5 parts.
[0014] Preferably, the mass percentage of the PBT resin in the PBT composite material is not less than 30%, preferably not less than 50%, and more preferably not less than 60%.
[0015] Preferably, the intrinsic viscosity of the PBT resin is 0.6-1dL / g, more preferably 0.7-0.8dL / g. The intrinsic viscosity of the PBT resin can be 0.6, 0.7, 0.8, 0.9, 1.0dL / g, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range. The intrinsic viscosity of the PBT resin of the present invention is the intrinsic viscosity at 25°C tested by the GB / T 14190-2017 method. Under the above-mentioned intrinsic viscosity of the PBT resin, the PBT composite material can maintain a low mold deposit quality and a high molding rate during the injection molding process.
[0016] Preferably, the glass fibers are chopped glass fibers.
[0017] Preferably, the average diameter of the glass fiber is 10-13 μm. The average diameter of the glass fiber can be 10, 11, 12, 13 μm, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0018] The use of chopped glass fibers in the PBT composite material system of the present invention can further improve the mold scale problem during the material injection molding process and accelerate the material molding.
[0019] Preferably, the mass of the glass fiber is 15-50% of the mass of the PBT resin, and more preferably, the mass of the glass fiber is 25-33% of the mass of the PBT resin.
[0020] The content of glass fiber is related to the degree of improving mold deposit and accelerating material molding. Within the above content range, it is more conducive to reducing mold deposit of PBT composite materials during the injection molding process and accelerating the molding rate.
[0021] Preferably, the mass of the anti-mold deposit additive is 0.8-3.5% of the mass of the PBT resin, and more preferably, the mass of the anti-mold deposit additive is 1.5-2.5% of the mass of the PBT resin.
[0022] The mold-deposit-resistant additive is a compound containing a 3-phenyl-2-acrylic acid structure. The content of the mold-deposit-resistant additive is related to the content of small molecules that can be captured during the injection molding process. Within the above-mentioned content range of the mold-deposit-resistant additive, the small molecules generated during the injection molding process can be effectively captured, and the mold deposits during the injection molding process can be significantly reduced, the crystallization temperature of the material can be increased, and the rate of material molding can be accelerated. In addition, the mold-deposit-resistant additive should not be excessive, otherwise the mold-deposit-resistant additive will be excessive, and the excess mold-deposit-resistant additive, as a small molecule substance that generates mold deposits, will increase the mass of the mold deposits and reduce the crystallization temperature, resulting in an increase in mold deposits.
[0023] Preferably, the auxiliary agent includes an antioxidant and a lubricant.
[0024] Further preferably, the antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis(3-laurylthiopropionate), and tris[2.4-di-tert-butylphenyl]phosphite; and the lubricant includes at least one of ethylene bisstearamide, montan wax, calcium stearate, and pentaerythritol tetrastearate.
[0025] In a fourth aspect, the present invention provides a method for preparing the PBT composite material, comprising the following steps: mixing PBT resin, anti-mold deposit additive, additive and glass fiber, melting them under light, and then extruding and granulating them to obtain the PBT composite material.
[0026] In the preparation of the PBT composite material, the present invention prepares the PBT composite material by melting under light, the mold-deposit-resistant additive first reacts with the terminal hydroxyl group on the PBT to cap part of the PBT, and then the carbon-carbon double bond in the acrylic acid group of the mold-deposit-resistant additive is polymerized by itself to form a four-membered ring macromolecule, thereby increasing its molecular weight, and the chemical structure is as shown in Formula II; compared with the structure of the mold-deposit-resistant additive itself, Formula II has a larger molecular weight and is more difficult to precipitate during the injection molding process, thereby avoiding the mold-deposit-resistant additive from precipitating and aggravating the mold-deposit problem; at the same time, the mold-deposit-resistant additive consumes part of the terminal hydroxyl group on the PBT in the process of forming a macromolecular capture agent, thereby capping part of the PBT, and the terminal carboxyl group carried by the capture agent can increase the proportion of the terminal carboxylic acid group in the system, thereby accelerating the molding of the material.
[0027]
[0028] Preferably, the melting temperature is 200-240° C., and the wavelength of the light is 250-320 nm.
[0029] In addition, the present invention also provides an application of the PBT composite material in the preparation of electronic appliances, in particular, in the preparation of connectors and controllers in the electronic appliance industry.
[0030] Compared with the prior art, the present invention has the following beneficial effects: by adding a mold deposit resistance additive to the PBT composite material, small molecules generated by PBT during the injection molding process can be captured, the small molecule content of the system can be reduced, the mold deposit problem can be improved, and the crystallization temperature of the material can be increased to a certain extent, thereby accelerating the molding of the material. DETAILED DESCRIPTION
[0031] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. The components and raw materials used in the embodiments and comparative examples of the present invention are the same unless otherwise specified.
[0032] PBT resin 1: PBT GX110, intrinsic viscosity: 0.6dL / g, Yizheng Chemical Fiber;
[0033] PBT resin 2: PBT GX111, intrinsic viscosity: 0.7dL / g, Yizheng Chemical Fiber;
[0034] PBT resin 3: PBT GX112, intrinsic viscosity: 0.8dL / g, Yizheng Chemical Fiber;
[0035] PBT resin 4: PBT GX121, intrinsic viscosity: 1.0 dL / g, Yizheng Chemical Fiber;
[0036] The chemical structure of the mold-proof additive is shown in Formula I below:
[0037]
[0038] Wherein, X1, X2, and X3 are each selected from any one of a hydrogen atom, an alkyl group, an alkoxy group, and a halogen.
[0039] Anti-mold deposit additive 1: 3-phenyl-2-acrylic acid, Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0040] Anti-mold deposit additive 2: 3-(4-chlorophenyl)-2-acrylic acid, Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0041] Anti-mold deposit additive 3: 3-(3-methylphenyl)-2-acrylic acid, Shanghai Jizhi Biochemical Technology Co., Ltd.;
[0042] Anti-mold deposit additive 4: 3-(2-bromophenyl)-2-acrylic acid, Shanghai Huayuan Century Trading Co., Ltd.;
[0043] Glass fiber 1: 10 μm in diameter, ECS10-4.5-534AKF, Jushi glass fiber;
[0044] Glass fiber 2: diameter 11 μm, ECS11-4.5-534A, Jushi glass fiber;
[0045] Glass fiber 3: diameter 13 μm, ECS13-4.5-534A, Jushi glass fiber;
[0046] Antioxidant 1: SONOX 1010, Shandong Sanfeng;
[0047] Antioxidant 2: RIANOX 412S, Tianjin Li’anlong;
[0048] Lubricant: PETS-AP, hair base.
[0049] Examples 1-17 and Comparative Examples 1-2
[0050] A method for preparing a PBT composite material comprises the following steps:
[0051] (1) According to the formula in Table 1-2, weigh PBT resin, antioxidant, lubricant, and mold deposit resistance additive respectively, mix them evenly, and then add them to the extruder;
[0052] (2) According to the formula in Table 1-2, glass fiber is added to the extruder from the side feed, fully melted and mixed evenly, the melting temperature is 200-240°C, and light with a wavelength of 280nm is applied to the homogenizing section of the extruder, extruded and granulated to obtain a PBT composite material.
[0053] Table 1
[0054]
[0055]
[0056] Table 2
[0057]
[0058] The PBT composite materials prepared in the above examples and comparative examples were subjected to injection mold fouling test and rapid molding effect test:
[0059] (1) Injection mold fouling test: Place a metal steel sheet at the mold exhaust port, and continuously inject 200 times at 260°C. Collect the mold fouling on the metal sheet and weigh it. The difference in mass before and after the metal sheet is used to characterize the size of the mold fouling.
[0060] (2) Rapid prototyping effect: The crystallization temperature of the PBT composite material is used to characterize the rapid prototyping effect. The higher the crystallization temperature of the PBT composite material, the faster the molding cooling, the shorter the cycle, and the faster the molding rate. The crystallization temperature is tested according to ISO11357-2011 differential scanning calorimeter.
[0061] The above test results are shown in Table 3.
[0062] Table 3
[0063]
[0064]
[0065] It can be seen from Example 1 and Comparative Example 1 that the present invention adds a mold-deposit-resistant additive in the preparation of the PBT composite material, so that the mold-deposit-resistant additive is polymerized into a macromolecular structure, and in the process of forming the mold-deposit-resistant additive with a macromolecular structure, the terminal hydroxyl groups in the system can be consumed, and the proportion of terminal carboxyl groups is increased. The increase in the proportion of terminal carboxyl groups helps to increase the crystallization temperature of the material, shortens the subsequent injection molding cycle, and accelerates the molding of the material. At the same time, the mold-deposit-resistant additive with a macromolecular structure captures small molecules in the system during the injection molding process, reduces the generation of mold deposits, and the mold-deposit-resistant additive with a macromolecular structure is not easy to precipitate, and will not further aggravate the mold deposit, thereby comprehensively achieving the effects of low mold deposit and rapid molding.
[0066] It can be seen from Examples 1-4 that the content of small molecular substances in PBT resins of different intrinsic viscosities is different. It can be seen from the examples that as the intrinsic viscosity of the PBT resin in Examples 2, 1, 3, and 4 increases, the mold deposit quality and the crystallization temperature gradually decrease. The intrinsic viscosity of the PBT resin can be selected to be 0.6-1L / g, and 0.7-0.8L / g is further preferred. At this time, the PBT composite material maintains a lower mold deposit quality and a higher molding rate during the injection molding process.
[0067] It can be seen from Examples 1, 5-7 that with the increase of the glass fiber content in Examples 5, 6, 1, and 7, the mold deposit mass first gradually decreases and then significantly increases, and the crystallization temperature gradually increases. When the glass fiber accounts for 15-50% of the mass of the PBT resin, and further preferably 25-33%, the mold deposit content is lower and the crystallization temperature is also higher.
[0068] It can be seen from Examples 1 and 8-9 that as the diameter of the glass fiber increases, the mass of the mold deposit gradually increases, the crystallization temperature gradually decreases, the diameter of the glass fiber increases, the shear increases, and the mass of the mold deposit increases to a certain extent; when the mass content of the glass fiber is the same, due to the difference in the diameter of the glass fiber, the number of glass fibers in the material is different. Since the glass fiber itself has a heterogeneous nucleation effect on the PBT resin, the crystallization temperature caused by the glass fiber with a lower diameter is relatively high.
[0069] It can be seen from Examples 1, 10-12 and Comparative Example 2 that as the content of the anti-mold deposit aid in Examples 10, 1, 11, 12 and Comparative Example 2 increases, the mold deposit mass first decreases and then increases, and the crystallization temperature gradually increases; when the content of the anti-mold deposit aid is low, the free PBT small molecules cannot be fully captured, resulting in low mold deposit and crystallization temperatures, and when the capture agent content is too high, the anti-mold deposit aid is excessive, and the excess anti-mold deposit aid, as a small molecule substance that produces mold deposit, increases the mold deposit mass and reduces the crystallization temperature, resulting in an increase in mold deposit. Therefore, in the system of the present invention, the mass of the anti-mold deposit aid accounts for 0.8-3.5% of the mass of the PBT resin, and more preferably 1.5-2.5%. At this time, the PBT composite material maintains a lower mold deposit mass and a higher molding rate during the injection molding process.
[0070] It can be seen from Examples 1 and 13-15 that, at the same weight, the groups in the anti-mold deposit additive are different, and the molar numbers of the anti-mold deposit additives in the system are different. The effect of the anti-mold deposit additive with a larger molar mass is smaller than that of the anti-mold deposit additive with a smaller molar mass, which leads to a certain degree of high mold deposit and a certain degree of low crystallization temperature.
[0071] It can be seen from Examples 1 and 16-17 that due to the different contents of the additive and PBT, the content of small molecules produced by degradation during the processing is different. When the additive content is high, it itself, as a small molecule substance, will cause high mold deposits. Therefore, when the components of the PBT composite material are within the weight parts required by the present invention, the PBT composite material can maintain a lower mold deposit quality and a higher molding rate during the injection molding process.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. Use of a compound of general formula (I) as a mold deposit resistance additive in a PBT composite material, characterized in that: The compound of general formula (I) is shown below: Wherein, X1, X2, and X3 are each selected from any one of a hydrogen atom, an alkyl group, an alkoxy group, and a halogen.
2. The use according to claim 1, characterized in that The compound of general formula (I) includes at least one of 3-phenyl-2-propenoic acid, 3-(4-chlorophenyl)-2-propenoic acid, 3-(3-methylphenyl)-2-propenoic acid and 3-(2-bromophenyl)-2-propenoic acid.
3. A PBT composite material, characterized in that: The invention comprises the following raw material components in parts by weight: 35-80 parts of PBT resin, 9-31 parts of glass fiber, 0.4-2.2 parts of the anti-mold deposit additive according to claim 1 or 2, and 0.4-1.6 parts of an additive.
4. The PBT composite material according to claim 3, characterized in that: Include at least one of the following: (A) the intrinsic viscosity of the PBT resin is 0.6-1dL / g; (B) the average diameter of the glass fibers is 10-13 μm; (C) The mass of the glass fiber is 15-50% of the mass of the PBT resin.
5. The PBT composite material according to claim 3, characterized in that: The mass of the anti-mold deposit additive is 0.8-3.5% of the mass of the PBT resin.
6. The PBT composite material according to claim 3, characterized in that: The auxiliary agents include antioxidants and lubricants.
7. The PBT composite material according to claim 6, characterized in that: The antioxidant includes at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, tetrakis(3-laurylthiopropionate), and tris[2.4-di-tert-butylphenyl]phosphite; the lubricant includes at least one of ethylene bisstearamide, montan wax, calcium stearate, and pentaerythritol tetrastearate.
8. A method for preparing the PBT composite material according to any one of claims 3 to 7, characterized in that: The steps include: The PBT resin, the anti-mold deposit additive, the additive and the glass fiber are mixed, melted under light, and then extruded and granulated to obtain the PBT composite material.
9. The method for preparing the PBT composite material according to claim 8, characterized in that: The wavelength of the light is 250-320nm.
10. Use of the PBT composite material according to any one of claims 3 to 7 in the preparation of electronic appliances.
Citation Information
Patent Citations
Low-mold-scale flame-retardant reinforced PBT composite material as well as preparation method and application thereof
CN112745642A
Attractive-appearance heat-resistant ASA composite material as well as preparation method and application thereof
CN118048000A
High flow polyester composition
US20070049667A1
Hyperbranched resin-toughened PBT engineering plastic composition
WO2016179769A1